USULAN PERBAIKAN TATA LETAK FASILITAS PABRIK PERALATAN LALU LINTAS DENGAN METODE ARC DAN ARD - Nusantara, Bangun; Andalia, Winny; Pratiwi, Irnanda (Nusantara of Engineering (NOE), 2023)
This study aims to discuss the flow of material movement to produce the layout of the signpost production facility at PT. Sarana Lalu Lintas, to reduce the distance of movement and material handling cost (OMH). The problem faced in the initial layout was the process flow in the production of signs that were not well arranged. The distance between spaces is far apart. Due to the distance between spaces, this has resulted in considerable material handling costs. The Activity Relationship Chart (ARC) and Activity Relationship Diagram (ARD) are carried out based on the degree of proximity between facilities and then a proposed layout is made. A redesign of the layout of the laboratory facilities was carried out to lower the distance of movement and the cost of handling materials. The results of the study using ARC and ARD obtained a decrease in the distance of movement to 1,350 meters and material handling costs (OMH) of Rp2,199,717. Efficiency produced in the proposed layout was 37.16%.